2007
DOI: 10.1016/j.bbrc.2007.06.017
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 ubiquitin ligase is essential for RANKL signaling and osteoclast differentiation

Abstract: Tumor necrosis factor receptor-associated factor 6 (TRAF6), the crucial adaptor molecule of receptor activator of NF-κB (RANK), plays an essential role in governing the formation of multi-nucleated osteoclasts. TRAF6 is a RING-dependent ubiquitin (Ub) ligase that in conjunction with Ubc13/ Uev1A catalyzes its own auto-ubiquitination via Lys63-linked poly-Ub chains. While the receptoradaptor function of TRAF6 in RANK signaling is well understood, the significance of its Ub ligase activity in this process remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 20 publications
(37 reference statements)
0
114
0
1
Order By: Relevance
“…Other laboratories have reported that RANKL signaling cannot be restored to TRAF6 KO monocytes by the reexpression of TRAF6[C70A] (17,39). This could be related to the problem discussed in the preceding section in refolding this E3 ligase-inactive mutant in MEFs to a conformation that can support signaling.…”
Section: Il-1 Signaling In Mefs Frommentioning
confidence: 99%
“…Other laboratories have reported that RANKL signaling cannot be restored to TRAF6 KO monocytes by the reexpression of TRAF6[C70A] (17,39). This could be related to the problem discussed in the preceding section in refolding this E3 ligase-inactive mutant in MEFs to a conformation that can support signaling.…”
Section: Il-1 Signaling In Mefs Frommentioning
confidence: 99%
“…Mutational analysis performed in authentic OC precursors using a chimeric receptor strategy showed that although a proximal TRAF6-binding site mediated NF-κB activation at the level of IκBα phosphorylation, two more distal sites, which also bind to TRAF2 and 5, could activate classical NF-κB as well [7]. Autoubiquitination of TRAF6 and interaction between aPKC and p62 are required for sustained NF-κB activation and OC differentiation [8,9]. CYLD is a negative regulator of TRAF6 ubiquitination and NF-κB activation, and its deletion enhances RANKL-mediated osteoclastogenesis [10].…”
Section: Rankl-induced Nf-κbmentioning
confidence: 99%
“…Protein expression and purification from Escherichia coli were performed as described previously for His-tagged proteins (17) or for glutathione S-transferase (GST)-tagged proteins (34).…”
Section: Cell Lines and Antibodiesmentioning
confidence: 99%